The Development Map and Research Direction On Education Of Islamic Moderation: A Bibliometric Study - Aprilia Hidayati; Ahmad Nurrohim; Mahmud Nasir (Institut Agama Islam An-Nawawi Purworejo, 2023)
Islamic education is a process of changing individual and communal behavior. Educational moderation is the bright path to the harmony of social, ecological, and spiritual relations. The purpose of this paper is to know the development map and research direction of Islamic moderate education. The research data is 96 articles obtained from the Scopus database, without taking into account data from other databases such as Google Scholar or WoS, from 2001 to 2023. Research data are selected and determined based on the functions and criteria set. The findings were analyzed by bibliometric analysis techniques using Excel, VOSviewer, and R/R-Studio with biblioshiny. The results of this study showed an annual article growth rate of 8.49%. The most publicity occurred in 2021. Indonesia is the country that contributes the most articles with 31 documents. Affiliation is held by the University Kebangsaan Malaysia. The most prolific authors were Adib-Hajbaghery, Hamzah, Paradise, and Razak